Socially Responsible Investments in Germany, Switzerland and the United States: An Analysis of Investment Funds and Indices - Michael Schröder (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2003)
The aim of this study is the analysis of so called socially responsible investments (SRI). First, the performance of SRI equity investment funds and equity indices is investigated using Jensens alpha as performance measure. The analysis considers market timing strategies of the fund management and takes publicly available information into account (conditional performance). In the second part sensitivities regarding macroeconomic factors are estimated and the third part investigates the investment style of the SRI funds and indices. It is found that most of the SRI assets have a similar performance than their benchmarks. Only a few funds and indices exhibit a relatively poor performance. As SRI funds and indices seem to have some specific risk-return characteristics (investment styles) that might be characterised as special investment vehicles different from conventional assets.
Keywords: G11; G23; Q20; Q01; 330; Socially responsible investing; performance measurement; investment style; investment funds; Investmentfonds; Unternehmensethik; Verantwortung; Umweltschutz; Wertpapieranalyse; Schätzung; Deutschland; Schweiz; Vereinigte Staaten; Jensen alpha